Bu‐Shen‐Huo‐Xue‐Fang modulates nucleus pulposus cell proliferation and extracellular matrix remodeling in intervertebral disk degeneration through miR‐483 regulation of Wnt pathway. Issue 12 (25th August 2019) - Yang, Shaofeng; Li, Linghui; Zhu, Liguo; Zhang, Chao; Li, Zhaoyong; Guo, Yantao; Nie, Ying; Luo, Zhenhua
Abstract: Intervertebral disk degeneration (IDD) has been widely considered as one of the main causes for low back pain, which can cause a severe impact to human health and huge economic burden to worldwide society. IDD pathogenesis can be affected by extensive degradation of extracellular matrix (ECM) and the hyperproliferation of nucleus pulposus (NP) cells. During the IDD process, expression of the ECM degradation enzymes matrix metalloproteinase and ADAMTS increases, whereas expression of ECM synthesis–related aggrecan and COL2A1 decreases. In addition, the Wnt signaling pathway is reportedly involved in the process of IDD. Bu‐Shen‐Huo‐Xue‐Fang (BSHXF), a Chinese traditional medicine formula that contains six Chinese traditional medicinal herbs, is widely used in the treatment of IDD. Herein, we obtained the serum containing BSHXF from BSHXF‐fed rat and demonstrated that the BSHXF promoted NP cell proliferation and ECM synthesis through the Wnt signaling pathway. By using DIANA online tools and luciferase reporter gene assays, we confirmed that miR‐483‐3p and miR‐23c regulated CTNNB1 and GSK3B, respectively, through direct targeting, thereby affecting the effect of BSHXF on NP cell proliferation and ECM synthesis through the Wnt signaling pathway. Taken together, we demonstrated the function and mechanism of BSHXF in regulating NP cell proliferation and ECM remodeling through the Wnt signaling pathway during IDD. Abstract : We demonstrated the function and mechanism of Bu‐Shen‐Huo‐Xue‐Fang (a Chinese traditional medicine formula) in regulating nucleus pulposus cell proliferation and extracellular matrix remodeling through the Wnt signaling pathway during intervertebral disk degeneration.